Effect of Varieties and Spacing on Radiation Efficiency, Growth and Yield of Sweet Corn (Zea mays saccharata Sturt.) in The Lebak Swamp Land - Majedi - (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
Corn is an important food crop in Indonesia which has a function as a source of food, a source of feed and the main ingredient for industry. Corn production in Hulu Sungai Utara Regency has increased from 2018-2020. However, it has not been able to meet market demand for corn because it is constrained by several factors such as lowland swamp land which is used as a place of cultivation with all the problems, namely periodically inundated land, low soil fertility, high soil acidity, toxic substances, lack of micro nutrients, organic matter still raw and others. From the aspect of cultivation technology, the use of superior varieties and proper spacing is influenced by environmental factors, especially climatic factors. The objectives of the study were: 1) Analyzing the interaction of varieties and planting distance on radiation efficiency and growth component of sweet corn (Zea mays saccharata Sturt.) in the lebak swamp land. 2) Analyzing the best varieties and the best planting distance for radiation efficiency and growth component of sweet corn (Zea mays saccharata Sturt.) in the lebak swamp land. This research was conducted in the lebak swamp land of ​​the STIPER Amuntai Experimental Garden, Muara Tapus Village, Hulu Sungai Utara Regency, South Kalimantan Province. At an altitude of ± 2 meters above sea level with coordinates of -2o28' South Latitude and 115o13